Can NO Signaling and Its Metabolism Be Used to Improve Nutrient Use Efficiency? Toward a Research Agenda - Buet, Agustina (2022)
One important issue to be faced by modern agriculture is ensuring an efficient use of the essential nutrients taken up from the soil by crops, thus helping to reduce the economic costs and by-side environmental effects derived from addition of fertilizers, which -frequently- involve the use of non-renewable resources. Improving use efficiency of the major nutrients contained in these fertilizers, nitrogen (N), phosphorus (P) and potassium (K), can be afforded through multiple strategies and must be thought in concert with the prevalence of a panoply of biotic and abiotic stresses. Therefore, simultaneous attention must be paid to the signaling network involved in setting Nutrient Use Efficiency (NUE) and to the acclimation of plants to a wide range of environments.